The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0265021506001931
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac protection by volatile anaesthetics

Abstract: Myocardial damage measured by cardiac troponin release could be reduced by volatile anaesthetics in coronary artery bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…Experimental data are supported by several clinical studies which showed less cardiac damage in patients receiving the volatile anesthetic desflurane compared to control patients [22][24]. Another study compared the effects of sevoflurane versus total intravenous anesthesia, in terms of postoperative cardiac troponin I release in patients undergoing noncardiac surgery.…”
Section: Discussionmentioning
confidence: 90%
“…Experimental data are supported by several clinical studies which showed less cardiac damage in patients receiving the volatile anesthetic desflurane compared to control patients [22][24]. Another study compared the effects of sevoflurane versus total intravenous anesthesia, in terms of postoperative cardiac troponin I release in patients undergoing noncardiac surgery.…”
Section: Discussionmentioning
confidence: 90%
“…The study revealed less release of CK-MB and troponin, indicating attenuated cardiac injury in the isoflurane group. The cardioprotective potential of various volatile anesthetics, applied during surgery, measured by a reduction in biomarkers of cardiac injury, has been confirmed by many authors [11-13,19,20]. A meta-analysis performed in 2007 clearly suggested that sevoflurane or desflurane is able to reduce the incidence of myocardial infarction and postoperative mortality after cardiac surgery [21].…”
Section: Discussionmentioning
confidence: 96%
“…A meta-analysis performed in 2007 clearly suggested that sevoflurane or desflurane is able to reduce the incidence of myocardial infarction and postoperative mortality after cardiac surgery [21]. Some of these studies even showed benefits with regard to mechanical ventilation and/or length of hospital stay [12,13]. Different windows of pharmacologic protection with early and late pharmacologic preconditioning by the use of volatile anesthetics have been described in the literature, both probably involving different signaling pathways, which are still not understood in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials comparing the use of these anesthetics to intravenous anesthetics prior to coronary artery bypass grafting (CABG) showed statistically significant reductions in peak troponin I levels, need for postoperative inotropic support, and need for length of stay exceeding seven days 161164 . In one study, a volatile anesthetic reduced one-year mortality 165 .…”
Section: Clinical Applications Of Pkc Regulatorsmentioning
confidence: 99%